EXTRACTION AND PURIFICATION OF CAROTENOID PIGMENTS SYNTHESIZED BY MARINE PHOTOSYNTHETIC BACTERIA AS A SOURCE OF NATURAL ANTIBIOTICS - Kayla Difa; Nursyirwani Nursyirwani; Ummi Mardhiah Batubara (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Marine photosynthetic bacteria are microorganisms with the potential to produce bioactive compounds in the form of carotenoid pigments, which can be utilized as a natural source of antibacterial agents. This study aims to characterize the carotenoid pigments produced by the marine photosynthetic bacterial isolate LD04 and to determine their potential antibacterial activity against the pathogenic bacteria Pseudomonas aeruginosa, Escherichia coli, and Vibrio harveyi. The study was conducted using an exploratory descriptive method, involving bacterial culture, antibacterial activity testing using the disc diffusion method, biomass production, pigment extraction using methanol, and purification and characterization using Thin Layer Chromatography (TLC) and High-Performance Liquid Chromatography (HPLC). LC analysis yielded a single major spot, indicating the presence of a dominant pigment component in the extract. Further characterization by HPLC at a wavelength of 450 nm produced a peak at a retention time of 6.35 minutes, whereas the astaxanthin standard was detected at 28.2 minutes. This difference in retention time suggests that the main compound in the extract is likely a xanthophyll or a more polar carotenoid derivative. Antibacterial activity testing showed that the pigment extract was able to inhibit the growth of E. coli and V. harveyi, but showed no activity against P. aeruginosa. The largest inhibition zone diameters were obtained for E. coli at 5.63 mm and V. harveyi at 1.23 mm, classified as weak inhibition according to CLSI standards. Based on the research results, it can be concluded that the carotenoid pigments from the marine photosynthetic bacterial isolate LD04 have potential as a source of natural antibacterial agents, particularly against E. coli and V. harveyi.